Back Cover Image, Volume 3, Number 2, June 2021. Issue 2 (15th June 2021) - Zeng, Jinjue; Xu, Chenyang; Gao, Tian; Jiang, Xiangfen; Wang, Xue‐Bin
Abstract : Back cover image : Three‐dimensional graphene (3DG) is the porous monolithic bulk of graphene, beyond graphene powders/fi lms, which is greatly preferred by some practical applications, e.g. electric double‐layer capacitors (EDLCs). In article number 10.1002/cey2.107, Xuebin Wang's group overviewed the synthesis methodology of 3DG porous monoliths, and they emphatically summarized the 3DGbased EDLCs. The paper also discusses current challenges about the 3DG and the EDLCs.